Detection and Dietary Exposure Assessment of Fluoroquinolones Residues in Chicken Meat from the Districts of Malang and Blitar, Indonesia - R. Widiastuti; E. Martindah; Y. Anastasia (Tropical Animal Science Journal, 2022)
The purpose of this study was to determine the presence of fluoroquinolones (enrofloxacin and ciprofloxacin) residues in fresh chicken meat and evaluate its consumption risk to the adult population in Indonesia. A total of 55 fresh chicken-meat samples were collected from Districts of Malang and Blitar, East Java Province, Indonesia, in April 2017. Detections of enrofloxacin and ciprofloxacin were carried out using high-performance liquid chromatography equipped with a PDA detector. It was found that ciprofloxacin was detected with a frequency of 67.3% at a maximum concentration of 275.00 ng/g. Enrofloxacin was detected with a frequency of 41.8% at a maximum concentration of 242.40 ng/g, or totally as a sum of enrofloxacin and ciprofloxacin residues detected in 76.4% samples at a maximum concentration of 367.50 ng/g. The estimated dietary intakes of ciprofloxacin and enrofloxacin were 44.90 ng/kg body weight/day and 7.91 ng/kg body weight/day, respectively, resulting in the hazard indexes of 0.0063 and 0.0013 for the consumptions of ciprofloxacin and enrofloxacin residues in chicken meat. Therefore, the risk associated with the consumption of ciprofloxacin and enrofloxacin residues in chicken meat by the adult population in Indonesia was considered negligible.